Synthesis and copolymerization of oligo(lactic acid) derived norbornene macromonomers with amino acid derived norbornene monomer: Formation of the 3D macroporous scaffold - Sutthira Sutthasupa (2018)
© 2015 Wiley Periodicals, Inc. Norbornene macromonomers 2 and 3 bearing 10- and 20-mers of lactide were synthesized by ring-opening polymerization of lactide using 5-norbornene-2, 3-exo-exo-dimethanol as an initiator and DBU as a catalyst. Macromonomers 2 and 3 were copolymerized with amino acid derived norbornene monomer 1, using the Grubbs 2nd generation ruthenium catalyst. The random and block copolymers with Mn's ranging from 28,000 to 180,000 were obtained almost quantitatively where the Mn's of the block copolymers were higher than those of the random ones. Three-dimensional macroporous structure polymers with average pore size of 10 μm could be found in poly(1) and the block co-polymer of 1 and 2 or 1 and 3 at the high ratio of 1. Meanwhile, poly(2) and poly(3) along with block and random copolymers with low ratio of 1 exhibit much larger pores in the range of 50-300 μm. The porosity increased with increase in the unit ratio of 1. The compressive strength of the porous structure of poly(2) and poly(3) was improved by the copolymerization with 1.